Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. II. Gekkonidae, Phyllodactylidae, Sphaerodactylidae - Ribeiro-Júnior, Marco A. (Zootaxa, 2015)
I present distribution data of all geckos (Gekkonidae, Phyllodactylidae and Sphaerodactylidae) known from the Brazilian Amazonia, totaling 19 species, belonging to nine genera. This represents six more taxa than previously reported for these families. Data were based on the direct examination of 23,094 specimens deposited in three North American and eight Brazilian museums. Most species (68.4%) are endemic to the Amazonia; non-endemic species are mainly associated with open dry (semideciduous) forest or open vegetation (savanna) enclaves in Amazonia. As a whole, three taxa are widespread in Amazonia, two are restricted to eastern Amazonia, two to western Amazonia, three to northern Amazonia (either widespread or restriced to parts of the Guiana region), one to southern Amazonia, one to southwestern Amazonia, and three to the southern peripheral portion of Amazonia. Additionally, four species have unique distributions and four species have a distribution that is congruent with one of the areas of endemism recognized for other organisms (birds and primates), of which two occur in the area of endemism of Guiana, one in Inambari, and one in Tapajós.